Molecular Identification of Different Bacteria isolated from Infected Wounds at Hayatabad Medical Complex Peshawar Pakistan - Syed Luqman Shuaib, Mohsina Haq, Bakht Biland Khan, Farishta Haq, Ihteshamul Haq, Ibrar Ahmad, Wahid Ullah, Azhar Nazir, Muhammad Farooq, Hasnain Israr, Shahid Hussain, Kamran Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Wound infections are one of the most common hospital acquired infections and are an important cause of morbidity and account for 70-80% mortality. The Purpose of the current study was to determine the commonest bacteria associated with wound infections at Hayatabad Medical Complex Peshawar January 2019 to June 2020. A total of 100 culture positive samples from patients with mean age of 6.2+0.25 were analyzed. Patient history and clinical findings were collected on a pre-coded form. Pus samples or wound swabs were collected from infected wounds and were analyzed through culturing and biochemical methods for aerobic bacteria. A total of 109 bacteria were isolated from 100 samples with almost same frequency of Gram positive cocci 54(49.54%) and Gram negative bacilli 55(50.45%). Most frequently isolated organism was S. aureus 45(41.28%) followed by Pseudomonas species 20(18.35%).From this study we conclude that Wound infection remains an ongoing problem which, although, cannot be completely eradicated, however by taking prompt control measures against the most commonly isolated organism and proper care of wound may lead to the minimum of wound infection.